Polydactyly in the Tyrrhenian wall lizard (Podarcis tiliguerta) - Antigoni Kaliontzopoulou; Daniele Salvi; Verónica Gomes; João Maia; Panagiotis Kaliontzopoulos (Acta Herpetologica, 2013)
Polydactyly is a fairly frequent phenomenon in tetrapod populations, but it is relatively rare in reptiles. Here we report the occurrence of polydactyly in a random sample of the Tyrrhenian wall lizard (Podarcis tiliguerta) from Sardinia. In the locality of Siniscola (NE Sardinia), we found two polydactylous female lizards, one of which showed polydactyly in one and the other in both hind limbs. This observation constitutes, to the best of our knowledge, the highest frequency of polydactyly ever reported in a single lizard population (4.54%). While providing a direct explanation for polydactyly is complicated, the genetic data available show that the two polydactylous individuals are not direct siblings, excluding the hypothesis of direct maternal inheritance of this condition.